Climate processes over the Himalaya – the added value from high resolution regional climate modelling - Karmacharya, J (2014)
The Himalaya plays a vital role in shaping the hydro-climate of South Asia and beyond, but their climate has not yet been monitored and modelled as well as some other regions. As the summer monsoon is the dominant climate system over South Asia, including the Himalaya, realistic simulation of the South Asian summer monsoon (SASM) should be a prerequisite for the satisfactory simulation of the Himalayan climate. The present research tests the assumption that higher resolution modelling will provide improved representation of the SASM, both regionally and over the Himalaya region. The first part of this research assesses the strength and stability of the temporal relationships between the monsoon rainfall indices (MRIs) and the large-scale monsoon circulation indices (MCIs), as a precursor to using such indices for model evaluation. The remainder of the thesis evaluates model performance in simulating various characteristics of SASM, mainly with regard to precipitation. In particular, the sensitivity of a regional climate model (RCM) simulation to domain size and added value of high resolution RCM simulation are evaluated. For this purpose, the Hadley Centre unified model - HadGEM is utilized in its regional and, in few instances, global configurations. The RCM simulations are performed at 0.44° and 0.11° horizontal resolutions and they are forced by the ERA interim dataset. Results show that i) the MRI-MCI relationship exhibits considerable low-frequency variability, ii) RCM simulation of SASM, particularly precipitation, shows sensitivity to domain size and simulation with a moderately sized domain that partially excludes bias prone equatorial Indian ocean outperform those with larger domains, iii) high resolution RCM simulation adds value in many aspects of SASM precipitation, including the seasonal mean, relative frequency distribution, extremes, and active and break monsoon composites, but the improvements are generally seen over the Indo-Gangetic plain rather than the Himalaya. The findings promote use of a high resolution RCM over a moderate sized domain (˜ 25,000,000 sq. km) for the realistic simulation of SASM, but the study needs to be repeated with multiple realizations and different RCMs before arriving at a robust conclusion.